Understanding perspectives of asthma among pulmonologists in Indian settings: results from a questionnaire-based survey - P. S., Tampi; Singh, Sheetu; Reza, Tanvir; Batra, Supreet; S. S., Yuvarajan; Rachel P., Roopa; Khobragade, Kunal; Doshi, Nitinkumar S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Asthma is associated with high morbidity and mortality in India. This survey was undertaken to explore the perspectives of pulmonologists towards in-clinic management of patients with asthma. Methods: It was a cross-sectional survey of pulmonologists conducted across India. It was formulated to provide unbiased observations of real-world clinical practice focusing on methods of diagnosis of asthma and its treatment preferences. Results: The participants included 805 pulmonologists, with the majority primarily treating patients with asthma (62%), chronic obstructive pulmonary disease (19%) and allergic rhinitis (19%). More than 86% of pulmonologists consider clinical symptoms, history of childhood asthma, family history, and chronic allergic rhinitis for initial diagnosis. About 19-23% prefer spirometry alone or in combination with family history for confirmation of asthma. The preferred inhaled corticosteroids-long-acting bronchodilator (ICS-LABA) combination was budesonide-formoterol amongst 83% of pulmonologists. For both dry powder inhaler (DPI) and metered dose inhaler (MDI) devices, fine particle fraction per cent and delivered dose were ranked as the two most important attributes. Conclusions: Asthma is the most prevalent diagnosis among patients treated by pulmonologists on the basis of clinical presentation and medical history. The most commonly used pharmacotherapy for the treatment of asthma comprises ICS-LABA, with budesonide-formoterol being the preferred combination. Fine particle fraction per cent and magnitude of delivered dose influence the choice of asthma inhaler prescriptions the most.